PEMANTAUAN ALIRAN SEDIMEN MELAYANG SUB-SUB DAS DI CITARUM HULU DALAM KAITANNYA DENGAN UMUR OPERASIONAL WADUK SAGULING - -, Edi Tri Haryanto (Bulletin of Scientific Contribution, 2006)
Monitoring suspended load transport flowing in to Saguling Reservoir has been conducted from August 2005 to January 2006 by means of measurements : water level, discharge, and suspensions of Upper Citarum River at Station Nanjung and its main tributaries at six other stations: Cikapundung, Cikeruh, Citarik, Cirasea, Cisangkuy, and Ciwidey River. Discharge and sediment suspension rating curve was made than compared with which measured and analyzed by the Institute of Ecology Padjadjaran University in 1982 and that also reported by Dewanti 1983. The results indicated that trend of sediment suspension transports was not significantly difference between that in 1982, although since 1992, total sediment depositions in the reservoir was slightly increase above deposition plan (4 million m3 per year). During the last seventy half years, the total deposition sediment was 67,832,078 m3, the life storage capacity was 167,689,000 m3. By using the assumptions of steady rate of deposition in the reservoir, the remaining operational age of Saguling reservoir was 25 years. The conclusions is that the life time of Saguling Reservoir for electric power generation still in plan. To halt worsening conditions of erosion rate in the Upper Citarum Watershed and sediment transport pattern in to the Saguling reservoir, integrated planning of watershed management system should be taken in to account..